Reconfigurable Poly(urea‐urethane) Thermoset Based on Hindered Urea Bonds with Triple‐Shape‐Memory Performance. Issue 12 (9th May 2019) - Jia, Yunchao; Ying, Hanze; Zhang, Yanfeng; He, Hui; Cheng, Jianjun
Abstract: Thermoset shape memory polymers (SMPs) have a series of advantages in practical applications when compared with thermoplastic SMPs. However, the reprocessing and reshaping of thermosets are difficult due to the covalent crosslinking which severely limits the reconfiguration of polymer networks even under high temperature. Here, hinered urea bond (HUB), a urea bearing a bulky substituent on its nitrogen atom that can reversibly dissociate to the corresponding bulky amine and isocyanate, is integrated into the poly(urea‐urethane) (PUU) crosslinked networks, enabling the networks to topologically reconfigure to other structures. Instead of having to cure the thermoset in a mold, the incorporation of HUBs can decouple the synthesis and shape‐forming steps, which is a huge advantage for the processing of thermoset materials compared to conventional thermosets. This new PUU thermoset shows a broad glass transition behavior and exhibits excellent triple‐shape‐memory performance. With the incorporation of this dynamic urea bonds, permanent shapes can be flexibly tuned via the network reconfiguration, which is often neglected but significant to the practical application of SMPs. Abstract : Dynamic hindered urea bonds (HUBs) are integrated into poly(urea‐urethane) (PUU) thermoset, enabling PUU to be topologically reconfigurable. The integration of different domains leads to a wide phase transition range, enabling the PUU to exhibit triple‐shape‐memory performance, which greatly broadens the potential for the application of shape transformable polymers.